Manufacturing method of powder magnetic core

By mixing coated and uncoated soft magnetic powders and using low-melting point glass, the method addresses cost increases in powder magnetic core production, ensuring insulation and enhancing magnetic properties.

JP2025006199AInactive Publication Date: 2025-01-17TOYOTA JIDOSHA KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023106846
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for manufacturing powder magnetic cores with insulating coatings increase costs due to the extensive use of insulating film, which affects the magnetic properties and production efficiency.

Method used

A method involving the mixing of coated and uncoated soft magnetic powders, with a maximum 40% uncoated content, and the use of low-melting point glass to ensure insulation and reduce costs.

Benefits of technology

This approach maintains insulation while reducing costs and improving magnetic properties by optimizing the use of insulating film and incorporating low-melting point glass coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025006199000001_ABST
    Figure 2025006199000001_ABST
Patent Text Reader

Abstract

To provide a manufacturing method of a powder magnetic core, which ensures insulation between soft magnetic powder particles by insulation treatment while suppressing an increase in cost caused by the insulation treatment.SOLUTION: A manufacturing method of a powder magnetic core includes a mixing step of preparing a mixture by mixing a first powder in which an insulating coating is coated on the surface of a soft magnetic powder and a second powder in which an insulating coating is not coated on the surface of a soft magnetic powder, and a molding step of compressing and molding the mixture, in which the content of the second powder is 40 mass% or less when the entire mixture is taken as 100 mass%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing a powder magnetic core. [Background technology]

[0002] Powder cores used in reactors for power conversion and the like are manufactured by compression molding soft magnetic powder. Such powder cores are required to not only exhibit high magnetic properties in an alternating magnetic field, but also to have low iron loss when used in an alternating magnetic field.

[0003] Patent Document 1 discloses a soft magnetic powder, a dust core, and a soft magnetic alloy made of an iron alloy containing Si and Al, the iron alloy being characterized in that, when the entire iron alloy is taken as 100% by mass, it contains 4.5 to 7.5% Si, 2.5 to 5.5% Al, a total of 10% or less of Si and Al, and the remainder: Fe. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-26749 A Summary of the Invention [Problem to be solved by the invention]

[0005] Patent Document 1 describes that soft magnetic powders having an alloy composition within the above-mentioned specific range can easily produce powder magnetic cores having, for example, high saturation magnetization, low coercive force, high maximum magnetic flux density, and small iron losses (hysteresis loss and eddy current loss).

[0006] Examples of iron loss include eddy current loss, hysteresis loss, and residual loss. It is particularly important to reduce eddy current loss, which increases with the frequency of the alternating magnetic field. Therefore, soft magnetic powders whose surfaces are coated with an insulating film are preferably used for manufacturing powder magnetic cores. The presence of the insulating film enhances the insulation between adjacent soft magnetic powders, and reduces iron loss, thereby obtaining powder magnetic cores with improved magnetic properties. However, the technology described in Patent Document 1 assumes that the surfaces of all soft magnetic powders are coated with an insulating film to enhance insulation, which results in a problem that the amount of insulating film increases, and the insulating process for forming the insulating film increases costs.

[0007] The present disclosure has been made to solve such problems, and aims to provide a method for manufacturing a powder magnetic core that ensures insulation between soft magnetic powders through insulation treatment while suppressing increases in costs due to the insulation treatment. [Means for solving the problem]

[0008] A method for producing a powder magnetic core according to one embodiment includes a mixing step of preparing a mixture by mixing a first powder in which an insulating coating is coated on the surface of a soft magnetic powder and a second powder in which an insulating coating is not coated on the surface of a soft magnetic powder, and a molding step of compressing and molding the mixture, in which the content of the second powder is 40 mass% or less when the entire mixture is taken as 100 mass%. Effect of the Invention

[0009] The present disclosure makes it possible to provide a method for producing a powder magnetic core in which the insulation between soft magnetic powder particles is ensured by the insulation treatment while an increase in cost due to the insulation treatment is suppressed. [Brief description of the drawings]

[0010] [Figure 1] 1 is a flowchart showing a method for manufacturing a powder magnetic core according to a first embodiment. [Diagram 2] FIG. 2 is a partial cross-sectional view that shows a schematic diagram of a powder magnetic core. [Diagram 3]4 is a graph showing the relationship between the content of the second powder and iron loss in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] First embodiment Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. However, the present disclosure is not limited to the following embodiments. In addition, the following description and drawings are appropriately simplified for clarity of explanation.

[0012] Fig. 1 is a flowchart showing a method for producing a powder magnetic core according to the first embodiment. As shown in Fig. 1, the method for producing a powder magnetic core 1 according to the present embodiment includes steps S1 and S2. Step S1 is a mixing step of preparing a mixture by mixing a first powder 21 in which the surface of a soft magnetic powder 10 is coated with an insulating coating 11, and a second powder 22 in which the surface of the soft magnetic powder 10 is not coated with an insulating coating 11. Step S2 is a compacting step of compressing and compacting the mixture. In the method for producing a powder magnetic core 1 according to the present embodiment, when the entire mixture (or the entire powder magnetic core 1) is taken as 100% by mass, the content of the second powder 22 is 40% by mass or less.

[0013] Here, Fig. 2 is a partial cross-sectional view that shows a schematic diagram of a powder magnetic core. As shown in Fig. 2, the powder magnetic core 1 produced by the method for producing a powder magnetic core 1 according to the present embodiment has a first powder 21 in which the surface of a soft magnetic powder 10 is coated with an insulating coating 11, and a second powder 22 in which the surface of the soft magnetic powder 10 is not coated with an insulating coating 11, and the content of the second powder 22 is 40 mass% or less when the entire powder magnetic core 1 is taken as 100 mass%. In the powder magnetic core 1 shown in Fig. 2, a low-melting glass coating 30 is interposed between the first powders 21, between the second powders 22, and between the first powder 21 and the second powder 22.

[0014] Each of the above steps will be described in detail. In the mixing step (step S1), first, a first powder 21 and a second powder 22 are prepared. In the first powder 21, the surface of the soft magnetic powder 10 is coated with an insulating coating 11. By coating the surface of the soft magnetic powder 10 with the insulating coating 11, the insulation between the soft magnetic powder particles 10 in the powder core 1 is improved. The content of the first powder 21 is preferably 60 to 90 mass % or less when the entire mixture (or the entire powder core 1) is taken as 100 mass %.

[0015] In the second powder 22, the surface of the soft magnetic powder 10 is not coated with an insulating coating 11. If the surface of the soft magnetic powder 10 is not coated with an insulating coating 11, the magnetic permeability of each soft magnetic powder 10 increases, improving the magnetic properties of the powder core 1. Therefore, by adjusting the content of the second powder 22 in the powder core 1 to within a range of 40 mass% or less, it is possible to adjust the magnetic properties while reducing the iron loss (eddy current loss) of the powder core 1.

[0016] The soft magnetic powder 10 used for the first powder 21 and the second powder 22 contains a ferromagnetic element such as Fe, Co, or Ni as a main component. From the viewpoints of handling, availability, cost, and the like, pure iron powder or iron-based alloy powder is preferable as the soft magnetic powder 10. The composition of the soft magnetic powder 10, which is an iron-based alloy powder, is not particularly limited, but can be appropriately adjusted in consideration of the magnetic properties of the dust core 1, the moldability of the mixture, the formability of the insulating coating 11, and the like.

[0017] The soft magnetic powder 10 may contain one or more modifier elements that can improve the magnetic properties and resistivity of the powder core 1, the moldability of the mixture, the formability of the insulating coating 11, and the like. Examples of such modifier elements include Mn, Cr, Mo, Ti, and Ni. In general, the total amount of modifier elements is preferably 10% or less. The soft magnetic powder 10 may contain unavoidable impurities.

[0018] The soft magnetic powder 10 constituting the first powder 21 is not particularly limited, but is preferably an iron-based alloy powder containing Fe as a main component and further containing Al. If the iron-based alloy powder contains Al, an insulating coating 11 containing aluminum oxide (Al2O3) can be formed on the surface of the soft magnetic powder 10. The insulating coating 11 is preferably an insulating coating 11 made of Al2O3, which is compatible with low-melting point glass described later, but may be an insulating coating 11 containing a compound other than Al2O3 (for example, an oxide such as silicon oxide or iron oxide, aluminum nitride (AlN), etc.), or may be an insulating coating 11 made of a compound other than Al2O3.

[0019] Furthermore, the soft magnetic powder 10 constituting the first powder 21 is preferably an iron-based alloy powder containing Si in addition to Al (Fe-Si-Al alloy powder). Si can contribute to improving the electrical resistivity of the soft magnetic powder 10, improving the resistivity (reducing eddy current loss) or improving the strength of the powder core 1, etc. Furthermore, if the iron-based alloy powder contains Si as well as Al, the insulating coating 11 made of Al2O3 can be easily formed.

[0020] The method for forming the insulating coating 11 on the surface of the soft magnetic powder 10 can be appropriately selected depending on the type of insulating coating 11. For example, when forming the insulating coating 11 of Al2O3 on the surface of the Fe-Si-Al alloy powder, a method of performing an oxidation treatment in which the Fe-Si-Al alloy powder is heated in an oxidizing atmosphere can be used. Specifically, the first powder 21 can be obtained by heating the Fe-Si-Al alloy powder at a temperature of 650 to 1000°C in the air.

[0021] The insulating coating 11 is preferably present uniformly or homogeneously on the outer surface of the soft magnetic particles, but may have some uncoated or non-uniform or heterogeneous portions. The thickness of the insulating coating 11 is, for example, 0.01 to 1 μm, and preferably 0.1 to 0.5 μm. If the coating is too thick, the magnetic permeability may decrease, which is not preferable. If the coating is too thin, a sufficient insulating effect may not be obtained, which is not preferable.

[0022] The soft magnetic powder 10 constituting the second powder 22 is not particularly limited, but is preferably an iron-based alloy powder containing Fe as a main component and containing Si (Fe-Si alloy powder). If the iron-based alloy powder contains Si, it is possible to improve the electrical resistivity of the soft magnetic powder 10, improve the resistivity of the powder core 1 (reduce eddy current loss), or improve the strength, as described above.

[0023] The manufacturing method of the soft magnetic powder 10 is not particularly limited. The soft magnetic powder 10 may be, for example, an atomized powder made of spherical particles. When an atomized powder made of spherical particles is used, the aggressiveness between particles is reduced, and a decrease in the resistivity value due to destruction of the insulating coating 11 or the like can be suppressed. The atomized powder may be a gas atomized powder obtained by spraying a dissolved raw material into an inert gas atmosphere such as nitrogen gas or argon gas, or a gas-water atomized powder obtained by spraying the dissolved raw material and then cooling it with water.

[0024] The particle size (median diameter D50) of the soft magnetic powder 10 is not particularly limited, but is, for example, 1 to 500 μm, and preferably 10 to 360 μm. If the particle size is too large, it is not preferable because it leads to a decrease in resistivity or an increase in eddy current loss. If the particle size is too small, it is not preferable because it leads to an increase in hysteresis loss, etc. Note that this particle size is determined by a sieve classification method in which a sieve of a specified mesh size is used for classification.

[0025] The specific surface area of ​​the soft magnetic powder 10 is not particularly limited, but is preferably 0.001 to 0.04 m 2 / g is preferable. The specific surface area can be the BET specific surface area of ​​the particles measured by the nitrogen gas adsorption method using the BET (Brunauer-Emmett-Teller) method. The total specific surface area of ​​the soft magnetic powders 10 constituting the second powder 22 in the mixture (or the dust core 1) is preferably smaller than the total specific surface area of ​​the soft magnetic powders 10 constituting the first powder 21 in the mixture (or the dust core 1). By using the soft magnetic powders 10 having a smaller particle size than the soft magnetic powders 10 constituting the first powder 21 as the second powder 22 and adjusting the content of the second powder 22 so that the total specific surface area is reduced, the second powder 22 is arranged between the first powders 21, and high insulation can be ensured.

[0026] When preparing the mixture, low-melting point glass may be added to obtain a powder magnetic core 1 with high resistivity and high strength. In that case, in the mixing step, low-melting point glass may be added to the first powder 21 and the second powder 22 to prepare a mixture in which the first powder 21, the second powder 22, and the low-melting point glass are mixed. This makes it possible to form a low-melting point glass coating 30 made of low-melting point glass so as to cover at least a portion of the surface of at least one of the first powder 21 and the second powder 22, as shown in FIG.

[0027] Examples of low-melting glass include silicate glass, borate glass, bismuth silicate glass, borosilicate glass, vanadium oxide glass, phosphate glass, etc. The low-melting glass has a softening point lower than the annealing temperature when the powder magnetic core 1 is annealed.

[0028] The content of the low-melting glass is preferably 0.05 to 5.0 mass% when the entire mixture (or the entire powder core 1) is taken as 100 mass%. When the content of the low-melting glass is 0.05 mass% or more, a sufficient low-melting glass coating 30 is easily formed, and a powder core 1 with high resistivity and high strength can be easily obtained. When the content of the low-melting glass is 5.0 mass% or less, deterioration of the magnetic properties of the powder core 1 can be effectively suppressed.

[0029] Here, the low melting point glass coating 30 may be a layer of fine particles having a particle size smaller than that of the soft magnetic powder 10, attached to the surface of at least one of the first powder 21 and the second powder 22. The particle size of such low melting point glass fine particles depends on the particle size of the soft magnetic powder 10, and is, for example, 0.1 to 100 μm, and preferably 0.5 to 50 μm. If the particle size of the low melting point glass fine particles is too small, it becomes difficult to manufacture and handle them, and if the particle size is too large, it becomes difficult to form a uniform low melting point glass coating 30. The particle size of the low melting point glass fine particles can be specified by a wet method, a dry method, a method of determining the particle size from the scattering pattern of irradiated laser light, a method of determining the particle size from the difference in sedimentation rate, a method of determining the particle size by image analysis, and the like. The low melting point glass coating 30 may be a layer of fine particles continuously attached to the surface of at least one of the first powder 21 and the second powder 22.

[0030] For example, when forming the low-melting glass coating 30, a fine particle powder made of low-melting glass, the first powder 21, and the second powder 22 may be mixed in a dispersion medium and dried, or the low-melting glass softened by heating may be attached to at least one of the first powder 21 and the second powder 22. When the low-melting glass coating 30 is composed of a layer of fine particles having a particle size smaller than that of the soft magnetic powder 10 attached to the surface of at least one of the first powder 21 and the second powder 22, it can become a continuous coating through the subsequent compression molding and annealing processes.

[0031] When preparing the mixture, a lubricant may be added to distribute the low-melting glass uniformly on the surface of the soft magnetic powder 10. In this case, in the mixing step, the low-melting glass and the lubricant may be added to the first powder 21 and the second powder 22 to prepare a mixture of the first powder 21, the second powder 22, the low-melting glass, and the lubricant. When mixing the first powder 21, the second powder 22, the low-melting glass, and the lubricant, they may be mixed while being heated at a temperature equal to or higher than the melting point of the lubricant (for example, 100 to 150°C). Since the lubricant melts by heating, the low-melting glass and the lubricant can be uniformly attached to the surface of the soft magnetic powder 10, thereby improving the moldability of the dust core 1.

[0032] Furthermore, the addition of a lubricant can reduce wear and plastic strain of the powder during compression molding, thereby reducing the coercivity and hysteresis loss of the powder core 1. The addition of a lubricant also reduces friction between powder particles and between the powder and a die, thereby preventing the insulating coating 11 from peeling off from the soft magnetic powder 10. The lubricant also makes it easier to remove the compact from the die.

[0033] Examples of the lubricant include powders of metal salts of stearic acid such as zinc stearate, lithium stearate, and calcium stearate, polyhydroxycarboxylic acid amides, fatty acid amides, paraffin, wax, natural or synthetic resin derivatives, etc. The content of the lubricant is preferably 0.05 to 3.0% by mass when the entire mixture (or the entire powder core 1) is taken as 100% by mass. If the content of the lubricant is too high, the density of the powder core 1 may decrease, which may reduce the strength, and this is not preferable.

[0034] Other additives may be added to the mixture as necessary within a range that does not impair the magnetic properties, such as the magnetic flux density, of the powder core 1. The first powder 21 and the second powder 22, or these powders and a fine particle powder made of low-melting point glass, may be bound together with an appropriate binding agent (binder).

[0035] In the compacting step (step S2), for example, the mixture is filled into a die having a cavity shape corresponding to the shape of the powder magnetic core 1, and then a predetermined pressure is applied to the mixture filled in the die. This allows the mixture to be compacted into a green body. The pressure applied during compression compacting is not particularly limited, but the higher the pressure, the higher the strength and magnetic flux density of the powder magnetic core 1 that is obtained. From this perspective, the pressure applied is, for example, 4 to 12 t / cm in surface pressure. 2 The mold temperature during compression molding is not particularly limited, but may be, for example, room temperature (for example, 5 to 35° C.) or warm temperature (for example, 70 to 200° C.).

[0036] The compact obtained in the compacting step can be used as the powder magnetic core 1, but the method for producing the powder magnetic core 1 according to the present embodiment preferably includes an annealing step of annealing the compact after the compacting step. The annealing temperature for annealing the compact is appropriately selected depending on the type of soft magnetic particles and low melting point glass, and is preferably, for example, 600 to 900°C. By annealing at 600°C or higher, the residual strain and residual stress introduced into the soft magnetic powder 10 during compression molding can be removed, and the coercive force and hysteresis loss of the powder magnetic core 1 can be reduced. In addition, by annealing at 900°C or lower, the insulating coating 11 can be prevented from becoming thinner. This annealing is preferably performed, for example, in an inert atmosphere.

[0037] When a mixture containing low-melting glass is annealed after compression molding, the annealing temperature for annealing the molded body is set to be higher than the softening point of the low-melting glass. This allows the low-melting glass to soften during annealing, and therefore it is possible to obtain a dust core 1 with high strength in which low-melting glass coatings 30 are interposed between the first powders 21, between the second powders 22, and between the first powders 21 and the second powders 22.

[0038] The above steps allow the production of the powder core 1. The use of the powder core 1 produced by the method for producing a powder core 1 according to this embodiment is not particularly limited, but the powder core 1 can be suitably used, for example, as a core for a reactor. A reactor can be formed by winding a wire such as a copper wire around a ring-shaped core, which is the powder core 1, so as to cover at least a portion of the core.

[0039] Next, the present disclosure will be described in further detail based on examples. Note that the present disclosure is not limited to the examples. In the examples, six types of dust cores with different contents of the second powder 22 were manufactured, and the iron loss of each dust core was evaluated.

[0040] (Example) [Manufacturing of dust cores] First, Fe-Si-Al alloy powder (gas water atomized powder) was prepared as the soft magnetic powder 10 used for the first powder 21. The Fe-Si-Al alloy powder was heated at 900°C for 120 minutes in air to obtain the first powder 21 as the Fe-Si-Al alloy powder having an insulating coating 11 of Al2O3 coated on its entire surface. The Fe-Si-Al alloy powder contained 3.0 mass% Si, 3.5 mass% Al, and the remainder was mainly Fe, had a particle size of 100 μm, and a specific surface area of ​​0.002 to 0.009 m. 2 / g. In addition, Fe-Si alloy powder (gas water atomized powder) was prepared as the soft magnetic powder 10 used for the second powder 22. The Fe-Si alloy powder contained 3.0 mass % Si and the remainder was mainly Fe, had a particle size of 80 μm, and a specific surface area of ​​0.003 to 0.01 m. 2 / g.

[0041] Then, the first powder 21 and the second powder 22 were put into a beaker as a container, and further, low-melting glass and a lubricant were put in. The low-melting glass was a glass powder (softening point 550°C) made of borosilicate glass. The lubricant was stearic acid monoamide (Alflo S-10 manufactured by NOF Corporation).

[0042] Then, when the whole mixture was taken as 100 mass%, the first powder 21, the second powder 22, the low-melting glass, and the lubricant were mixed while being heated to 100 to 150° C. in such a ratio that the content of the second powder 22 was 0 mass%, 10 mass%, 20 mass%, 30 mass%, 40 mass%, or 50 mass%, the content of the low-melting glass was 2 mass%, the content of the lubricant was 0.5 mass%, and the remainder was the first powder 21. After mixing for 15 minutes in this manner, the mixture was cooled to 40 to 70° C. to prepare a mixture.

[0043] Next, the mixture obtained is poured into a ring-shaped mold, and the mold temperature is set to 20°C and the surface pressure is set to 4 to 12 t / cm 2The compact was compressed under the above conditions to obtain a ring-shaped compact having an outer diameter of 39 mm, an inner diameter of 30 mm, and a thickness of 5 mm. The compact was then placed in a heating furnace and annealed in a nitrogen atmosphere at an annealing temperature of 600 to 900°C for 30 minutes to produce a powder core as a ring test piece. In this manner, six types of powder cores with different contents of the second powder 22 were produced. Each of the produced powder cores has the first powder 21 in which the surface of the soft magnetic powder 10 is coated with the insulating coating 11, the second powder 22 in which the surface of the soft magnetic powder 10 is not coated with the insulating coating 11, and the low-melting glass coating 30 interposed between the powders.

[0044] [Iron loss measurement] The iron loss of the six manufactured powder magnetic cores was measured by the following method. Each powder magnetic core was wound with 90 turns of excitation wire and 90 turns of detection wire using a φ0.5 mm copper wire. The iron loss was measured at 0.1 T and 20 kHz using an AC magnetic measuring device. The results are shown in Figure 3.

[0045] Fig. 3 is a graph showing the relationship between the content of the second powder and iron loss in the examples. The horizontal axis of the graph shown in Fig. 3 shows the content (mass%) of the second powder 22. The vertical axis of the graph shown in Fig. 3 shows the increase or decrease in iron loss. It can be said that the lower the iron loss value, the higher the insulation. As can be seen from the results in Fig. 3, it was confirmed that when the content of the second powder 22 is 40 mass% or less, the increase in iron loss can be effectively suppressed without impairing the insulation.

[0046] Here, for example, when a powder core is manufactured using a mixture that does not contain the second powder 22, the insulation between the soft magnetic powder particles 10 is ensured by the presence of the insulating coating 11, so that although eddy current loss can be reduced, there is a problem that a powder core having high magnetic properties cannot be obtained. This can be caused by the fact that the magnetic permeability of each soft magnetic powder particle 10 decreases because each soft magnetic powder particle 10 is coated with the insulating coating 11.

[0047] In contrast, the manufacturing method of the powder magnetic core 1 according to this embodiment makes it possible to obtain a powder magnetic core 1 containing a first powder 21 in which the surface of the soft magnetic powder 10 is coated with an insulating coating 11, and a second powder 22 in which the surface of the soft magnetic powder 10 is not coated with an insulating coating 11 in a proportion that does not impair the insulation between the soft magnetic powders 10.

[0048] With this configuration, the insulating coating 11 of the first powder 21 improves the insulation between the soft magnetic powder particles 10, and since it is not necessary to cover the surfaces of all of the soft magnetic powder particles 10 with the insulating coating 11 in order to improve the insulation, it is possible to reduce the materials and the like required for the insulation treatment to form the insulating coating 11. Therefore, according to the manufacturing method for the powder core 1 according to this embodiment, it is possible to ensure the insulation between the soft magnetic powder particles 10 by the insulation treatment while suppressing an increase in costs due to the insulation treatment.

[0049] Furthermore, when the surface of the soft magnetic powder 10 is coated with an insulating coating, the strength of the powder core may decrease as the amount of the insulating coating increases depending on the material (e.g., resin) of the insulating coating. In contrast, in the manufacturing method of the powder core 1 according to the present embodiment, the strength of the powder core 1 can be increased by interposing the low-melting point glass coating 30 between the powder particles.

[0050] In addition, the present disclosure is not limited to the above embodiment, and can be appropriately modified within the scope of the present disclosure. For example, instead of adding a lubricant in the mixing process, a lubricant may be applied to the inner wall surface of the mold in the molding process, and then the mixture may be filled into the mold and compression molded. In this case, it is preferable to perform compression molding while heating the mold. [Explanation of symbols]

[0051] 1 powder magnetic core 10 Soft magnetic powder 11 Insulation coating 21 1st powder 22 2nd powder 30 Low melting point glass coating

Claims

[Claim 1] a mixing step of mixing a first powder having an insulating coating on the surface of the soft magnetic powder and a second powder having no insulating coating on the surface of the soft magnetic powder to prepare a mixture; a molding step of compressing and molding the mixture; having The method for producing a powder magnetic core, wherein the content of the second powder is 40 mass% or less when the entire mixture is 100 mass%.

Citation Information

Patent Citations

  • Method of manufacturing dust core

    JP2009295613A

  • Composite soft magnetic material and method for producing the same

    JP2010185126A

  • Mixed powder for powder magnetic core, and powder magnetic core

    JP2015213148A

  • Manufacturing method of dust core

    JP2020053536A

  • Composite magnetic material, metal composite core using composite magnetic material, and manufacturing method of composite magnetic material

    JP2022052083A